The Effect of Vitamin D Supplementation in Overweight or Obese Type 2 Diabetic Patients with Vitamin D Deficiency and Dyslipidemia - Sahar Shahriari (International Journal of Nutrition Sciences, 2018)
Background: Vitamin D supplementation was shown to reduce obesityrelated oxidative stress and inflammation among overweight or obese people as well as improving glycemic control and lipid profile in type 2 diabetic (T2D) patients. This study was conducted to determine the effect of vitamin D supplementation on metabolic biomarkers, oxidative stress and systemic inflammation in overweight or obese T2D patients with vitamin D deficiency and dyslipidemia. Methods: In this randomized, double-blind placebo-controlled clinical trial, 60 individuals with T2D, vitamin D deficiency and BMI greater than 25 kg/m2 were randomly divided in two groups to receive either vitamin D (50000 IU, once a week) or placebo (1000 mg corn oil, once a week) for eight weeks. At the entry and end of study, blood samples were collected to evaluate serum high sensitive C-reactive protein (hs-CRP), fasting blood sugar (FBS), glycated hemoglobin (HbA1c) malondialdehyde (MDA), total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL) and triglycerides (TG). Results: At the end of the study, serum FBS (P=0.04), TG (P=0.02) and hs-CRP (P=0.02) levels significantly decreased in the vitamin D supplemented group in comparison to the control group. Supplementation with vitamin D was associated with significant improvements in serum 25 –OH vitamin D levels when compared to the control group. Conclusion: This study indicates that eight weeks supplementation of vitamin D may improve lipid, glycemic and inflammatory indices in overweight or obese T2D patients with vitamin D deficiency and dyslipidemia.